Analisis Kesenian Rudat “Gaya Cigadogan” di Kampung Cigadog Desa Cigadog Kecamatan Leuwisari - Yeni Handayani; Asep Wasta; Wan Ridwan Husen (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
This research aims to analyze one of the traditional arts, Rudat. The traditional art that still exists in West Java is Rudat art in Kampung Cigadog, Cigadog Village, Leuwisari District. Rudat art is vocal art accompanied by tarebang and kendang bajidor percussion, as well as silat movements and chanting of sholawat. The presentation and performance structure of Rudat art in Cigadog involve several elements, including movements, dancers, accompanying music, and costumes. The Rudat performance "Gaya Cigadogan" consists of preparation, middle stage, and final stage. The issue addressed in this research is the presentation form and performance structure of Rudat art. The objective of this research is to describe the presentation form and performance structure of Rudat art. This study employs a qualitative method with a descriptive analysis approach, where the researcher aims to present all research findings from the field. Data collection techniques used include observation, interviews, and documentation.